An analysis of statutory general debarment in the South African finance markets - Nemukula, Gift (University of the Witwatersrand, Johannesburg, 2025)
This dissertation critically examines the debarment process outlined in the Financial Advisory and Intermediary Services (FAIS) Act within the context of South Africa's constitutional framework. The proliferation of debarment cases has raised concerns about the alignment of these actions with constitutional protections of the right to work. The dissertation establishes two primary objectives: first, to delineate the limited circumstances under which debarment can legitimately occur while safeguarding fundamental rights, and second, to assess the extent to which the FAIS Act's debarment procedures adhere to this framework. Through an analysis of legal principles, constitutional rights, legislative provisions, case law, and empirical data, the dissertation identifies the absence of clear guidelines and procedural safeguards governing the debarment process. It highlights inconsistencies in application and the potential for unjustified limitations on individuals' right to work. The dissertation concludes by advocating for the development of a systematic framework that upholds constitutional principles, ensures procedural fairness, and promotes regulatory integrity in debarment decisions within the financial services industry.
A research report submitted in fulfillment of the requirements for the Master of Commerce, in the Faculty of Commerce Law and Management, School of Business Sciences, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Right to work; statutory debarment; legal limitations; common law; constitutional law; administrative law; South African law; Financial Advisory and Intermediaries Services Act; SDG-8: Decent work and economic growth